2004
DOI: 10.1111/j.1365-2265.2004.02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clomiphene and raloxifene on gonadotrophin secretion in postmenopausal women: evidence of nongenomic action

Abstract: These results demonstrate for the first time that in contrast to Cl, R does not exert oestrogenic effects on basal gonadotrophin secretion. Although the antioestrogenic action of these drugs was evident only after pretreatment with E2, both R and Cl stimulated GnRH-induced gonadotrophin secretion in oestrogen-deprived women. It is hypothesized that these two compounds sensitize the pituitary to GnRH through mechanisms not involving the oestrogen receptor complex (nongenomic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…It has also been suggested that clomifene may inhibit the estradiol-dependent proliferation of endometrial epithelial cells by inhibiting the recruitment of SRC1 to ERa and thus estradioldependent ER transactivation (Amita et al, 2010). A summary of several clinical trials revealed that clomifene is as effective as tamoxifen in inducing ovulation for infertility management, although results from another study suggest that the actions on gonadotropin-releasing hormone levels may be nongenomic in nature (Garas et al, 2004;Steiner et al, 2005).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 93%
“…It has also been suggested that clomifene may inhibit the estradiol-dependent proliferation of endometrial epithelial cells by inhibiting the recruitment of SRC1 to ERa and thus estradioldependent ER transactivation (Amita et al, 2010). A summary of several clinical trials revealed that clomifene is as effective as tamoxifen in inducing ovulation for infertility management, although results from another study suggest that the actions on gonadotropin-releasing hormone levels may be nongenomic in nature (Garas et al, 2004;Steiner et al, 2005).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 93%
“…It is possible therefore that various pathways can be involved in the control of PRL release from the pituitary lactotrophs. It has also been suggested that raloxifene and clomiphene, although binding to oestrogen receptors, can also affect the function of pituitary gonadotrophs via nongenomic mechanisms 13 . Nevertheless, regardless of all these mechanisms, it seems from the present data that the main pathway through which E2 stimulates PRL secretion is via the oestrogen receptors.…”
Section: Discussionmentioning
confidence: 46%
“…Changes in gonadotrophin values during these experiments have already been reported 13 . Basal hormone values were calculated as the mean of the values at −15 and 0 min.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations